Modelling the volatility transmission and conditional correlations between A and B shares in forecasting value-at-risk - Da Veiga, Bernardo; Chan, Felix; Mcaleer, M. (Elsevier Science, 2008)
The aim of this paper is to investigate the effect of the Chinese B share market reform on the conditional correlation and information transmission between A and B Shares issued in the Shanghai and Shenzen stock exchanges. Daily returns for the Shanghai A share index (SHA), Shanghai B share index (SHB), Shenzen A share index (SZA) and Shenzen B share index (SZB) are used for the period 6 October 1992 to 8 February 2005. The impact of the reform on the volatility spillovers and volatility transmission were found to be significant. The results also suggest that all pairs of conditional correlations increase dramatically over the period analysed, but such increases began well before the reforms to the B share market. The importance of accommodating such an increase in conditional correlations and changes in the information transmission mechanism when estimating value-at-risk (VaR) thresholds is analysed. The results suggest that accommodating the B share market reform may not be particularly important in empirical analyses of volatility transmission.